HUBUNGAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The purpose of this study was to determine whether there is a relationship and how big is the relationship between learning independence and mathematics learning outcomes for STKIP Paris Barantai students. This study uses a quantitative approach assisted by correlation. This type of quantitative research with the help of correlation through sampling steps, data collection using questionnaires and interviews, validation of research instruments with validity and reliability tests, data analysis techniques by means of normality tests and then hypothesis testing. The results showed that there was a positive and significant relationship between learning independence and learning outcomes. Based on the results of the analysis that has been carried out, it is obtained that tcount is 2.12 and ttable is 2.04, because tcount > ttable, the decision was taken that Ho is rejected, meaning that there is a relationship between learning independence and mathematics learning outcomes for STKIP Paris Barantai students. The relationship between independent learning and mathematics learning outcomes of STKIP Paris Barantai students can be seen from the percentage of contributions that give 13.88% and is determined by other factors such as motivation, interests, talents, family by 86.12%. Keywords: Independent Learning, Learning Outcomes, STKIP-PB Students.